Model Komunikasi Nabi Yusuf dalam Menanggulangi Krisis Pangan di Mesir: Refleksi Terhadap Ayat Al-Quran Surat Yusuf - Ridwan, Ridwan (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2024)
This study examines the communication strategies employed by Prophet Yusuf in addressing the food crisis in Egypt, as narrated in the Quran. The main issue discussed is how Prophet Yusuf's communication approach facilitated strategic decision-making to resolve the crisis. The purpose of this study is to explore and understand how Prophet Yusuf utilized processes such as self-reflection and emotional regulation to formulate policies and take actions during a critical situation. The research employs a qualitative approach with textual analysis of the Quran and its interpretations. Additionally, a communication analysis approach is used to identify communication processes, including self-reflection, internal dialogue, and personal evaluation, in the context of strategic decision-making. This approach links psychological and communication aspects to better understand Prophet Yusuf's role as a leader during a crisis. The findings reveal that Prophet Yusuf relied on deep self-reflection, effective emotional management, constructive internal dialogue, and strategic planning as key elements in tackling the food crisis. The implications of this research contribute to the field of communication studies, particularly in the context of crisis management, by emphasizing the importance of communication as a foundation for effective decision-making. These findings are expected to inspire the application of communication strategies in addressing crises across various fields of life.